Experimental analysis on drilling process of composite laminates - Sivasankaran, Praveena Nair (2008)
This thesis deals with carbon fiber reinforced plastics (CFRP) composites, an advanced material which is widely used in manufacturing aircrafts because of their unique mechanical and physical properties. The research mainly involved drilling of CFRP. This study focused on analyzing the thrust force and delamination against drilling parameters namely feed rate, spindle speed and type of tool materials. Also, the optimal parameters were chosen using an optimization method called D optimal. It was observed that the higher the feed rate and spindle speed employed, the higher the thrust force and delamination that occurs. The optimal parameters obtained were 221.72mm/min for feed rate, 2000 rpm for spindle speed and the most suitable tool chosen was the SPF drill. A verification test was conducted and the percentage error obtained for delamination was 5.6% and for thrust force was only 2.3%. This shows, that the optimal parameters obtained is reliable as it could improve the process considerably.The results of this study could be used as a reference for further research and studies on drilling of CFRP. -Author-